Equivalence scales based on revealed preference consumption expenditure microdata: The case of West Germany - Joachim Merz; Jürgen Faik (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 1992)
Equivalence scales are a prerequisite for any economic well-being comparison with measures on income distribution, inequality and poverty. This paper provides equivalence scales based on revealed preference consumption microdata for West Germany 1983. It is a part of a joint US and German research project comparing equivalence scales with consistent methods and similar microdata bases, recent income and consumption surveys of both countries. We concentrate on a single equation expenditure method with different Engel approaches as well as on a complete demand system approach.The complete demand system approach provides true, constant utility based equivalence scales and is specified by an extended linear expenditure system (ELES). While the Engel methods traditionally focus on food expenditures, the multiple equation expenditure system takes into account a full market basket with all its interdependencies and relative prices.Our equivalence scale study for West Germany based on actual available individual consumption expendituredata shows a variety of interesting results with regard to different goods and services baskets as well as to different household composition effects including the situation of the elderly, of the families with married couples and single mothers, and the cost of children. Our consumption results finally are compared to further consumption, expert, and subjective based equivalence scales. – – Äquivalenzskalen sind eine notwendige Voraussetzung für jeden ökonomischen Wohlfahrtsvergleich mit Informationen zur Einkommensverteilung, zur Ungleichheit und zur Armut. Das vorliegende Diskussionspapier stellt Äquivalenzskalen auf der Basis von Konsum-Mikrodaten offenbarter Präferenzen für die Bundesrepublik Deutschland 1983 vor. Es ist ein Teil eines amerikanisch-deutschen Forschungsprojektes, das Äquivalenzskalen mit konsistenten Methoden und ähnlichen Mikrodaten vergleicht, und zwar den aktuellsten verfügbaren Einkommens- und Verbrauchsstichproben beider Länder. Wir konzentrieren uns auf ein Einzelgleichungsmodell mit unterschiedlichen Engel-Ansätzen und einen kompletten nachfragetheoretisch fundierten Systemansatz.Der Systemansatz liefert wahre, nutzenbasierte Äquivalenzskalen und wird durch ein erweitertes lineares Ausgabensystem (ELES) spezifiziert. Während die Engel-Verfahren traditionellerweise auf die Nahrungsmittelausgaben rekurrieren, zieht das multiple Ausgabensystem einen vollständigen Warenkorb mit all dessen Interdependenzen und relativen Preisverhältnissen in Betracht.Unsere Äquivalenzskalen-Studie für die Bundesrepublik Deutschland auf der Basis von aktuell verfügbaren individuellen Konsumausgaben zeigt eine Vielfalt interessanter Resultate bezüglich der verschiedenen Güter-/Dienstleistungs-Körbe ebenso wie verschiedene Effekte der Haushaltsstruktur, welche die Situation der Alten, die Familien mit Ehepaaren und alleinstehenden Müttern sowie die Kinderkosten einbeziehen. Unsere Ausgaben-Resultate werden abschließend mit weiteren verbrauchs-basierten, experten-basierten und subjektiven Äquivalenzskalen verglichen.
Keywords: I30; I32; D30; D31; 330; alternative equivalence scales; Germany; USA; distribution of income; inequality; poverty; Alternative Äquivalenzskalen; Deutschland; USA; Einkommensverteilung; Ungleichheit; Armut